2017
DOI: 10.1093/molehr/gax053
|View full text |Cite
|
Sign up to set email alerts
|

Zona pellucida-binding protein 2 (ZPBP2) and several proteins containing BX7B motifs in human sperm may have hyaluronic acid binding or recognition properties

Abstract: An EU Marie Curie Sklodowska Initial Training Network Scholarship, supporting Ms Torabi, is gratefully acknowledged. This project was also supported and funded by the Efficacy and Mechanism Evaluation Programme, a UK MRC and NIHR partnership (Grant No 11/14/ 34). There is no conflict of interest in relation to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Therefore, dysfunction in the ubiquitin-related pathway might have relevance in the physiological functions of the sperm. Furthermore, the effects of PLBD1 gene polymorphism on the biological function of the sperm is still unclear, even though it has been reported that PLBD1 is implicated in the fertilization processes [47]. Moreover, the PLBDI gene is related to 12 GO enriched terms, such as "lipid metabolic process", "signal transduction", and "kinase activity", suggesting the important role of the gene in various sperm biological functions.…”
Section: Snp Associations With Post-thaw Semen Qualitymentioning
confidence: 99%
“…Therefore, dysfunction in the ubiquitin-related pathway might have relevance in the physiological functions of the sperm. Furthermore, the effects of PLBD1 gene polymorphism on the biological function of the sperm is still unclear, even though it has been reported that PLBD1 is implicated in the fertilization processes [47]. Moreover, the PLBDI gene is related to 12 GO enriched terms, such as "lipid metabolic process", "signal transduction", and "kinase activity", suggesting the important role of the gene in various sperm biological functions.…”
Section: Snp Associations With Post-thaw Semen Qualitymentioning
confidence: 99%
“…Sperm capacitation is a recognized phenomenon associated with acquisition of hyperactive motility comprising a complex set of highly regulated molecular and physiological events. As mature spermatozoa are no longer engaged in nuclear gene expression (Oliva, 2006; Jodar et al, 2013), understanding the role of protein modifiers, cell-cell communication and signaling pathways is essential (Baldi et al, 1996; Halet et al, 2003; De Jonge, 2005; Visconti et al, 2011; Buffone et al, 2012; Signorelli et al, 2012; Cuasnicú et al, 2016; Barrachina et al, 2018; Torabi et al, 2017b). For instance, many studies have correlated capacitation with an increase in cholesterol efflux from the sperm membrane (Visconti et al, 2002; Gadella et al, 2008) that modulates intracellular levels of calcium and bicarbonate ions (Visconti et al, 2011; Battistone et al, 2013; Li et al, 2014; Puga Molina et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…25 However, in fact, the concentration of sp24666 was found to increase significantly from Cor 5 to Cor 6 in our study. P13611-associated proteins were highly expressed in spermatozoa that recognized the zona pellucida, 26 and the protein GO: 0009987 was highly expressed in highly active spermatozoa. 27 These proteins only increased 10-fold in the initial stage of the vas deferens transition from the cauda and were not highly expressed in the caput, corpus, and cauda.…”
Section: Discussionmentioning
confidence: 99%